Plan estratégico publicitario de los centros artesanales de alfarería y cerámica de la victoria y Pujilí respectivamente, para promover el turismo del cantón. - Estrella Molina, Darwin Nicolay (2015)
This strategic publicity plan of craft centers pottery and ceramics; Victoria parish and Pujili respectively, promoting the tourism in the canton, it allowed to detect in those sectors that one of fundamental problems is the lack of dissemination its native products, as well as its places to visit making this an attractive place for tourism of owns and strangers. The main objective was to create visual identifications, in photographed of ceramics and exhibitions, route maps, signposting, educational in phography for inhabitants such sectors; obtaining as beneficiaries commercial sector and special handicraft sector by increasing the number of visitors and tourists. This investigative work was applied, some investigation methods such as inductive-deductive and analytic-synthetic; it was worked using a sample of population, proceeding to gather information, it showed as result that was necessary elaboration strategic publicity plan, including the various crafts that are manufactured as well as places to make attractive the visit in this parish, allowing imminent economic growth; so it becomes a reference order and progress of the Ecuador.